Rapid hot marking tool - Sivarao, Subramonian; Abdul Rahim, Samsudin (2015)
The present invention relates to an apparatus for marking an article using stamping foil on at least one surface, comprising; a tool head; a tool body attached to the tool head; a concentration rod heater for heating or cooling of concentration; a thermostat to measure the temperature at one end of tool head; and a thermocouple sensor to control heating or cooling temperature of the heater, wherein the thermocouple sensor control the heating or cooling temperature by using the thermostat having at least one set point temperature.